An integrated analysis of QTL mapping and RNA sequencing provides further insights and promising candidates for pod number variation in rapeseed (Brassica napus L.). (December 2017) - Ye, Jiang; Yang, Yuhua; Chen, Bo; Shi, Jiaqin; Luo, Meizhong; Zhan, Jiepeng; Wang, Xinfa; Liu, Guihua; Wang, Hanzhong
Abstract Background As the most important yield component in rapeseed (Brassica napu s L.), pod number is determined by a series of successive growth and development processes. Pod number shows extensive variation in rapeseed natural germplasm, which is valuable for genetic improvement. However, the genetic and especially the molecular mechanism for this kind of variation are poorly understood. In this study, we conducted QTL mapping and RNA sequencing, respectively, using the BnaZNRIL population and its two parental cultivars Zhongshuang11 and No.73290 which showed significant difference in pod number, primarily due to the difference in floral organ number. Result A total of eight QTLs for pod number were identified using BnaZNRIL population with a high-density SNP linkage map, each was distributed on seven linkage groups and explained 5.8–11.9% of phenotypic variance. Then, they were integrated with those previously detected in BnaZNF2 population (deriving from same parents) and resulted in 15 consensus-QTLs. Of which, seven QTLs were identical to other studies, whereas the other eight should be novel. RNA sequencing of the shoot apical meristem (SAM) at the formation stage of floral bud primordia identified 9135 genes that were differentially expressed between the two parents. Gene ontology (GO) analysis showed that the top two enriched groups were S-assimilation, providing an essential nutrient for the synthesis of diverse metabolites, and polyamine metabolism, serving as second messengers that play an essential role in flowering genes initiation. KEGG analysis showed that the top three overrepresented pathways were carbohydrate (707 genes), amino acid (390 genes) and lipid metabolisms (322 genes). In silico mapping showed that 647 DEGs were located within the confidence intervals of 15 consensus QTLs. Based on annotations ofArabidopsis homologs corresponding to DEGs, nine genes related to meristem growth and development were considered as promising candidates for six QTLs. Conclusion In this study, we discovered the first repeatable major QTL for pod number in rapeseed. In addition, RNA sequencing was performed for SAM in rapeseed, which provides new insights into the determination of floral organ number. Furthermore, the integration of DEGs and QTLs identified promising candidates for further gene cloning and mechanism study.